PENGARUH GOOD GOVERNANCE TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN PANGKAJENE DAN KEPULAUAN - Indriana Indriana (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
This study aims to determine the effect of Good Governance on Local Government Performance Pangkajene and Kepulauan. The type of research used in this study is quantitative by using descriptive statistical analysis method or SPSS 16. The data is processed is the result of questionnaires from the statement of employees of Pangkep District office. Data analysis techniques using simple linear regression formula and descriptive statistical test through SPSS 16 application. Based on the results of data analysis techniques using the formula used to produce the conclusion that the financial performance of local government of Pangkep district is very influential seen from the level of financial performance of local governments Pangkep district.